Epilepsy the intersection of neurosciences, biology, mathematics, engineering and physics - Osorio, Ivan. (Boca Raton, Fla. : CRC Press, 2011)
"Integrating the studies of epilepsy, neurosciences, computational neurosciences, mathematics, physics, engineering, and medicine, this volume provides the first means to a clear, structured, and enriching multidisciplinary perspective for developing students, researchers, and clinicians in the field of epilepsy. The text gives up to date information on the state of current research, possible future research, and clinical directions in the fields of epilepsy and seizure dynamics. Clear illustrations that illustrate the patterns of brain electrophysiology and behavioral manifestations are provided to aid comprehension. The authors include extensive references in each chapter to enhance further study"--Provided by publisher.
section 1. Foundations of epilepsy -- section 2. Foundations of engineering, math, and physics -- section 3. The challenge of prediction -- section 4. The state of seizure prediction : seizure prediction and detection -- section 5. The state of seizure prediction : seizure generation -- section 6. The state of seizure prediction : seizure control -- section 7. The state of seizure prediction : technology -- section 8. Nocturnal frontal lobe epilepsy : a paradigm for seizure prediction?
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Epilepsy; Electronic books